Culture and Money in the Nineteenth Century Abstracting Economics - Bivona, Daniel; Tromp, Marlene (Ohio University Press, 2016)
Since the 1980s, scholars have made the case for examining 19th-century culture, particularly literary output, through the lens of economics. Bivona and Tromp have collected contributions that push New Economic Criticism in new directions.Spanning the Americas, India, England, and Scotland, this volume adopts a global view of the cultural effects of economics and exchange. Contributors use the concept of abstraction to show how economic thought and concerns around money permeated all aspects of 19th-century culture, from the language of wills to arguments around the social purpose of art.The characteristics of investment and speculation; the symbolic and practical meanings of paper money to the Victorians; the shifting value of goods, services, and ideas; the evolving legal conceptualizations of artistic ownership are all essential to understanding nineteenth-century culture in Britain and beyond.